Fatima Meer, Memories of Love and Struggle (Historia, 2021)
The role of women continues to be neglected in the documenting of historical events, as it has been ever since the dawn of historiography. According to Winnie Mandela in the foreword of this book, South Africa is “still a patriarchal society, in which men are more recognised than women” (p 13). The life of Fatima Meer (1928–2010) is a case in point. Born to a newspaper editor father; literacy, education and justice formed the bedrock of Meer’s life but it is for her political activism that she is best remembered. Yet, despite the influential role she played in political activism, Meer is not a political figure who is often remembered and recognised. However, she was a prolific author, with some sources ascribing more than 40 books to her pen in addition to her work as a sociology academic. According to Shamim in the introduction of this book, Meer began to draft her autobiography in the year 2000 while compiling a book on her late husband Ismail Meer. Despite suffering a stroke in 2002 which confined Fatima to a wheelchair for the last 7 years of her life, she continued to work on her autobiography although it was only in 2017 that the book was finally published.
Keywords: women; Winnie Mandela; Fatima Meer